Efektivitas Aroma Terapi Lavender Dalam Mengurangi Mual Dan Muntah Pada Ibu Hamil Trimester 1 - Diajeng Retno Noviyati; Nila Widya Keswara (Journal of Innovative and Creativity, 2025)
Introduction: Pregnancy marks the onset of a biological process that starts with the release of an egg, followed by its fertilization, implantation in the uterus, and continues with the growth and development of the fetus until birth. Every phase of pregnancy presents a critical period that demands both mental and physical adaptation due to hormonal changes and the bodily strain from the expanding uterus and surrounding tissues. Among the earliest signs experienced are nausea and vomiting, which may stem from either psychological stress or physiological shifts. The purpose of this research is to examine how lavender aromatherapy influences nausea and vomiting among women in their first trimester of pregnancy. Method: This research employed a pre-experimental design using a one-group pre-test post-test approach without a control group. The study involved comparing the participants' scores before and after the intervention. A total of 24 first-trimester pregnant women were selected as participants using purposive sampling, with data collected through questionnaire forms. This indicates that there was a measurable difference between the pre-test and post-test outcomes. Therefore, it can be concluded that lavender aromatherapy had a beneficial impact in alleviating nausea and vomiting among first-trimester pregnant women in Lebakharjo Village, Ampelgading in 2025. Conclusion: Lavender aromatherapy may serve as an alternative non-pharmacological approach to help relieve nausea and vomiting in women during the first trimester of pregnancy.